Diagnóstico del nivel de cumplimiento del Plan de Desarrollo y Ordenamiento Territorial del Gobierno Autónomo Descentralizado parroquial de Taquil 2019-2023 - Guiñaguazo Robalino, Maria del Cisne (2023)
The purpose of this research was to identify the programs and projects by component contained in the Development and Territorial Planning Plan of the Autonomous Decentralized Parish Government of Taquil 2019-2023, to this end, the objectives set were met, carrying out a documentary review and the interview with the president of the parish council of Taquil which helped to detail the activities that have been carried out in each of the programs and projects. in addition, management indicators were applied to the programs and projects of the Development and Land Use Plan of the Decentralized Autonomous Government parish of Taquil 2019-2023 that were identified in such a way that the diagnosis of the level of compliance with the Development and Territorial Planning Plan of the Autonomous Decentralized Government of Taquil 2019-2023. For this, it was necessary to use the inductive, analytical and systematic methods which allowed the analysis of the components, programs and projects of the Development Plan and Territorial Planning of the parish Taquil and the use of traffic lights established by the technical secretariat plans Ecuador where it determines the percentages of the parameters to be evaluated, these being the following: fulfilled, partially fulfilled, unfulfilled and extemporaneous (no information found). In addition, specific techniques were used to meet the objectives set, such as interviews and documentary review. Resulting in 40 projects of which 23 of these are in extemporaneity which means that no information is found, 13 projects that despite their execution could not be fulfilled so they are classified as unfulfilled, 1 project that is partially fulfilled and 7 projects that have been able to crystallize within the Taquil parish being cataloged as fulfilled. Keywords: Development Plan and Land Management, diagnosis, level, projects, Taquil